2014 IEEE Symposium on Security and Privacy 2014
DOI: 10.1109/sp.2014.38
|View full text |Cite
|
Sign up to set email alerts
|

Cloak and Swagger: Understanding Data Sensitivity through the Lens of User Anonymity

Abstract: Abstract-Most of what we understand about data sensitivity is through user self-report (e.g., surveys); this paper is the first to use behavioral data to determine content sensitivity, via the clues that users give as to what information they consider private or sensitive through their use of privacy enhancing product features. We perform a large-scale analysis of user anonymity choices during their activity on Quora, a popular question-and-answer site. We identify categories of questions for which users are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…The privacy implications of our findings are even more alarming when considering the prominent role that platforms like Twitter play in protests and other forms of social activism [36]. Indeed, a substantial number of users choose to not reveal their actual identity on Twitter, and prior work has found a correlation between the choice of anonymity and the sensitivity of topics in tweets [54] 1 and other online posts [53].…”
Section: Introductionmentioning
confidence: 90%
“…The privacy implications of our findings are even more alarming when considering the prominent role that platforms like Twitter play in protests and other forms of social activism [36]. Indeed, a substantial number of users choose to not reveal their actual identity on Twitter, and prior work has found a correlation between the choice of anonymity and the sensitivity of topics in tweets [54] 1 and other online posts [53].…”
Section: Introductionmentioning
confidence: 90%
“…Our proposal is based on the existence of a mechanism that is able to determine the topics discussed by the pieces of information that are exchanged in OSNs (i.e., the messages). Topics here can be categories predefined by the underlying OSN infrastructure [54]; usergenerated tags like Flickr categories [53]; or categories or tags extracted from images [66,80], videos [3], geolocation information [45], or text [57,74,12].…”
Section: Topic Analysismentioning
confidence: 99%
“…As pointed out in [36], there is no universal definition of what constitutes sensitive content. For this analysis, we create a second dataset by selecting several broad topic categories that are widely considered sensitive and/or controversial by many-pornography, escort services, sexual orientation, religious and racial hatred, online drugs, and guns.…”
Section: Followers Of Sensitive and Non-sensitive Accountsmentioning
confidence: 99%
“…A study about 4chan, an image board website, showed that online communities can succeed despite being fully anonymous and extremely ephemeral [5]. By analyzing a question-and-answer websiteQuora, Peddinti et al show that it is possible to gain a novel understanding of users' perspectives on content sensitivity via a data-driven analysis of their usage of anonymity features of the website [36].…”
Section: Data Driven Studiesmentioning
confidence: 99%
See 1 more Smart Citation